Increases in plasma neurotensin levels and brain neurotensin receptors were associated with brain pathology in obese, insulin‐resistant rats: Molecular and cell biology/neurodegeneration and neuroprotection. (7th December 2020) - Saiyasit, Napatsorn; Chunchai, Titikorn; Apaijai, Nattayaporn; Pratchayasakul, Wasana; Sripetchwandee, Jirapas; Chattipakorn, Nipon; Chattipakorn, Siriporn C.
Abstract: Background: Our previous studies reported that long‐term high‐fat diet (HFD) consumption caused not only obese‐insulin resistance, and peripheral oxidative stress, but also brain pathologies, including increased brain oxidative stress, neuronal death, and dendritic spine loss. Neurotensin (NT) is an endogenous tridecapeptide, in which has been expressed in peripheral and central nervous system. Alterations of NT levels have been associated with several neuropathological conditions such as Alzheimer's disease, and obesity associated eating disorders. However, the association between the level of plasma NT, brain NT receptor (NTR), and peripheral/brain pathologies under HFD‐induced obese‐insulin resistance is still unclear. The present study hypothesizes that an increase in peripheral/brain NT are associated with the peripheral/brain pathologies in time‐dependent manner of HFD consumption. Methods: Male Wistar rats were received either a normal diet (ND) or HFD for 12 and 40 weeks (n=4‐6 per diet/each time point). At the end of each time point, plasma NT levels and metabolic parameters were determined. Brains were collected to measure the levels of hippocampal reactive oxygen species (ROS), the dendritic spine densities, the levels of brain NT, the expression of NTR, and apoptotic‐related proteins after being sacrificed. Results: An increase in plasma NT level and gut NTR1 expression (Figure 1A‐B), the metabolic disturbances, peripheral oxidative stress, as indicated by increasing the level of serum malondialdehyde, and systemic inflammation as indicated by increasing the level of serum lipopolysaccharide of 12‐ and 40‐week HFD‐fed rats were observed, when compared to ND‐fed rats at the same time point. Additionally, increased hippocampal ROS production, and decreased dendritic spine density (Figure 1C) were found in 12‐ and 40‐week HFD‐fed rats. However, the expression of brain NTR1 (Figure 1D) and brain apoptotic‐related proteins were significantly increased in only 40‐week HFD‐fed rats. Conclusion: These findings suggest that the alterations of peripheral NT level and brain NTR are associated with peripheral/brain pathologies after chronic HFD consumption. Therefore, an increase in plasma NT level would be one of the early biomarker prior to the development of brain pathologies in obese condition.